Electrical Activities Detected from the Experimentally-induced Trigger Points in Human Subjects - ITOH, Kazunori; OKADA, Kaoru; KAWAKITA, Kenji (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2002)
Electrical activities detected from the experimentally-induced trigger points in human subjects. Objectives : To examine the pathogenic mechanisms of the trigger points, electrical activities were recorded from the experimentally-induced trigger points. Methods : Nine healthy volunteers who gave informed consent were used. The adjustable loads were set around the third finger and repetitive eccentric contraction was loaded on the extensor digital muscles. The subjects were asked to keep the position as long as possible. The loadings (about 10s) were continued until his all-out effort and were repeated 3 times with 5 min resting periods. The electrical activities in the skin, fascia and muscle of the trigger point and non-tender region of palpable band and 10mm outside the band were recorded on the second day after the eccentric exercise. Results : Repetitive eccentric exercise produced a trigger point within the palpable band, which developed on the second day after the exercise. Electrical activities were detected only when the electrode tip was located in or near the fascia of the trigger point and there were subjective dull pain sensations. When the radial nerve was blocked by lidocaine, the needle EMG activity could not be recorded. Conclusions : These results suggest that the EMG activities are the result of nociceptive reflex, and the sensitized nociceptors in the fascia of the palpable band might be a substrate for the trigger point.